Leather waste into functional materials: composite nanoarchitectonics, energy systems, and environmental applications - Zheng, A. L.T.; Rajoo, K. S.; Manivel, C. M.; Teo, E. Y.L.; Marzuki, O. F.; Boonyuen, S.; Chung, E. L.T.; Andou, Y. (Springer, 2025)
The global leather industry generates large volumes of chromium (Cr)-containing solid waste, creating significant environmental risks to water systems and public health. This mini review highlights recent advances in converting leather residues into high-value materials for water purification and sustainable energy applications. Activated carbon (AC) derived from leather waste has demonstrated superior adsorption performance for heavy metals, dyes, and emerging contaminants, with removal efficiencies exceeding 95% for Cr and pharmaceutical compounds. Integration of leather-based carbons with photocatalysts such as BiOX and TiO₂ has enabled efficient photodegradation of industrial pollutants, supporting low-cost treatment of tannery effluents. In parallel, leather-derived collagen fibers have been engineered into triboelectric nanogenerators and battery electrodes, achieving open-circuit voltages of up to 231 V and specific capacitances of 550 F/g. These technologies demonstrate the potential of leather waste as a renewable feedstock for clean energy generation and storage. Key challenges remain in Cr stabilization, standardization of processing protocols, and scaling up pilot studies to industrial levels. Future work should integrate life-cycle assessment (LCA) and techno-economic analyses (TEA) to ensure safe, cost-effective deployment. By focusing on water remediation and energy harvesting, this review establishes a circular economy framework where leather waste transitions from an environmental liability to a resource for sustainable water and energy systems.